2009
DOI: 10.1210/jc.2008-1712
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Somatostatin Analogs on a Growth Hormone-Releasing Hormone Secreting Bronchial Carcinoid,in Vivoandin VitroStudies

Abstract: In this case of a GHRH-producing bronchial carcinoid, we demonstrated that SOM230 was a potent inhibitor of GHRH production in vitro and was at least equally potent compared with OCT. Therefore, SOM230 may be a potential therapeutic agent to control GHRH secretion in ectopic acromegaly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 32 publications
5
23
0
1
Order By: Relevance
“…The siNET cell line KRJ-I demonstrated equal mRNA expression levels for SSTR1 and SSTR2 [3]. In most studies where the quantitative mRNA expression levels of SSTRs were studied, SSTR2 was more highly expressed than SSTR1 [40,41,42,43,44]. In general, there is a predominant expression of SSTR1 and SSTR2 mRNA in NETs, with highly variable mRNA expression levels [40,45].…”
Section: Discussionmentioning
confidence: 99%
“…The siNET cell line KRJ-I demonstrated equal mRNA expression levels for SSTR1 and SSTR2 [3]. In most studies where the quantitative mRNA expression levels of SSTRs were studied, SSTR2 was more highly expressed than SSTR1 [40,41,42,43,44]. In general, there is a predominant expression of SSTR1 and SSTR2 mRNA in NETs, with highly variable mRNA expression levels [40,45].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the prevalence of zonulysis and phakodonesis has been extensively reported with PEX [1, 7, 14, 16,40,41,42,43,44]. Moreno et al [11] found a significantly higher incidence of iridophakodonesis in eyes with PEX having light-colored irides than in those with dark irides.…”
Section: Discussionmentioning
confidence: 99%
“…In many studies cataract surgery in the presence of PEX has been reported to be associated with increased risk of intraoperative and postoperative complications such as zonular dialysis, vitreous loss, prolonged corneal edema, sustained inflammatory reaction and lens decentration [6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25]. Zonular instability, poorly dilating pupils, corneal endothelial changes and breakdown of the blood-aqueous barrier are the leading factors in increased intraoperative and postoperative complications in eyes with PEX [7, 14,26,27,28,29,30,31]. …”
Section: Introductionmentioning
confidence: 99%
“…Treatment: Surgical removal of the tumor producing this ectopic hormone is the mainstay of therapy especially when no metastasis is detected with the resolution of acromegaly being evident with the first weeks of therapy [117][118]. Systemic therapy is necessary in patients with metastatic or inoperable disease and this includes chemotherapy and somatostatin analogues [119][120].…”
Section: /12mentioning
confidence: 99%